Applied Scientific Paper Proposal: Optimizing Radar Operation While Sailing in Rough Weather - Ach Akmal Alfianu Rossi; Dety Sutralinda; Teguh Pribadi; Anak Agung Ngurah Ade Dwi Putra Yuda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Maritime shipping faces high risks due to rough weather that impairs visibility and increases the potential for collisions, especially in congested waters such as the Strait of Malacca. This study aims to identify optimal radar operation and supporting efforts for navigational officers when the MT. Ginga Lion is sailing in the moderate sea. Using a descriptive qualitative approach with a case study design, the navigational officer population was purposively sampled (captain, chief officer, second officer AB). Instruments included observation, in-depth interviews, and documentation; data analysis followed the Miles and Huberman model with NVivo 14. The results showed that adjustments to Gain, Rain, Sea Clutter, and a combination of S-Band (long range) and X-Band (precision detection) radars were effective in overcoming rain clutter, supported by routine checks and navigational briefings. The conclusion confirms that the integration of technical, human resources, and procedures significantly improves navigational safety.